2013
DOI: 10.1177/0961000613477677
|View full text |Cite
|
Sign up to set email alerts
|

Information literacy and inquiry-based learning: Evaluation of a five-year programme of curriculum development

Abstract: Inquiry-based learning describes a range of learner-centred pedagogies increasingly employed in Higher Education where students learn through engaging in open-ended research and inquiry. It is acknowledged that this type of pedagogical approach requires advanced information literacy capabilities in students, and that there is a need to support the development of information literacy in inquiry-based learning curricula. This paper reports on the evaluation of a selection of curriculum development projects under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 53 publications
1
36
0
Order By: Relevance
“…Approaches promoting student-directed inquiry are well suited for ill-structured, authentic problems. Their solution requires commitment, the engagement in messy processes, and the creation of collective knowledge (Bissola & Imperatori, 2017;McKinney, 2014;Minocha et al, 2017;Peterson, 2004). These conditions are typical for PBL and IBL.…”
Section: Problem-and Inquiry-based Learningmentioning
confidence: 99%
See 2 more Smart Citations
“…Approaches promoting student-directed inquiry are well suited for ill-structured, authentic problems. Their solution requires commitment, the engagement in messy processes, and the creation of collective knowledge (Bissola & Imperatori, 2017;McKinney, 2014;Minocha et al, 2017;Peterson, 2004). These conditions are typical for PBL and IBL.…”
Section: Problem-and Inquiry-based Learningmentioning
confidence: 99%
“…IBL is a problem-or question-driven approach that integrates inquiry in terms of student-led investigations in order to strengthen the linkages between teaching and research in universities. Forms of inquiry include, for example, literature-based research, data collection, research drawing on questions and methods pre-specified by lecturers, applied research addressing practical issues, simulations, and role-plays (Aditomo, Goodyear, Bliuc, & Ellis, 2013;McKinney, 2014). IBL resembles PBL.…”
Section: Problem-and Inquiry-based Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the study by McKinney (2013) reported the evaluation of development projects undertaken at a United Kingdom university focusing on IL and on the development of IL capabilities to support learning. The results showed that students developed individual IL capabilities and learned how to effectively use library resources.…”
Section: Information Literacy Projectsmentioning
confidence: 99%
“…Harada and Yoshina (2004);Hmelo-Silver et al (2007);Chu et al (2011);McKinney (2013), among others, argue that there is evidence pointing to the effectiveness of pedagogical approaches based on projects for the improvement of learning outcomes.…”
Section: Introductionmentioning
confidence: 99%